PENGARUH JALAN KERETA API TERHADAP SIMPANG BERSINYA PATRANG JEMBER - Faruq Al Qomar; Irawati . .; Rofi Hamduwibawa (Universitas Muhammadiyah Jember, 2017)
Simpang signaling Jl. Moch Seruji - Jl. DR. Soebandi and Jl. Slamet Riyadi is geometrically comprised of three arms (south, west and north), located in Jember Town, Patrang District. This intersection serves various types of highway transportation vehicles (light vehicles, heavy vehicles, motorized and non-motorized vehicles), as well as access to public transportation within the City to Arjasa terminal. In addition, approximately 20 meters west of the intersection there is a railway track connecting Jember and Banyuwangi districts. Thus the oprasional intersection signaled DR. Soebandi is quite a potential sabagai point of traffic problems and transportation system of the city.Operational analysis of the intersection is done by analyzing the performance of intersection which includes degree of saturation, delay time, and queue length. The method used is Manual Capacity of Indonesia Road Capacity (MKJI 1997).From the results of this study shows that the intersection of DR. Soebandi with the volume of vehicles this year is still effective in performance, as well as the singkron of the way head of the train in the west of the intersection is fairly still able to accommodate the vehicle that is accommodated when the train passes. Keywords : Oprasional optical performance analysis, (MKJI 1997)